THE INFLUENCE OF TEACHER CREATIVITY IN THE LEARNING PROCESS OF STUDENT LEARNING OUTCOMES IN THE EDUCATION OF ISLAMIC RELIGIOUS EDUCATION CLASS VIII SMP PGRI 01 BUMI AGUNG - Wahyu Stiawan; Mr Supean Chemo; Miftahur Rohman; Khairul Hapizin; Hirlan Hirlan (RETEL Journal (Journal on Publication of The Research on Teaching and Language), 2019)
Educational institutions should ideally prioritize all aspects of learning both cognitive, affective and psychomotor. However, educational institutions at this time the learning process undertaken by educators tends to be the achievement of curriculum material targets. Teacher creativity is needed to achieve maximum learning outcomes. The purpose of this study was to determine the effect of teacher creativity in the learning process on student learning outcomes in subjects of Islamic religious education class VIII SMP PGRI 01 Bumi Agung Academic Year 2013/2014 ". Research by the author is a quantitative study in the processing of data using samples from the population. The sample used in this study amounted to 30 students drawn from a population of 30 students of class VIII, consisting of 1 class. The method used in this study is the method of observation, questionnaires and documentation. The results of the analysis of the author's data using the Product Moment formula, the results obtained are rxy of 0.468 greater than the table, both for a significant level of 5% or 1%, namely 0.361 0.468> 0.463. So this shows that there is an influence of teacher creativity in the learning process with student learning outcomes in Islamic religious education subjects Class VIII SMP PGRI 01 Bumi Agung Academic Year 2013/2014. Thus, it needs to be improved in the creativity of teachers in the learning process to obtain the specified learning outcomes.